Scavenging for solid waste in Kinshasa: A livelihood strategy for the urban poor in the Democratic Republic of Congo. (October 2015) - Simatele, Danny; Etambakonga, Clément Longondjo
Abstract: Scavenging for solid waste has come to play an important role in contributing to the urban food basket of poor households in Kinshasa. This development has taken place in the context of profound poverty levels exacerbated by political instability. Using field based data collected in three sites, the paper examines the role that solid-waste scavenging contributes to household livelihoods. It is argued that although solid waste scavenging is largely neglected in urban development and planning policies, it plays a key role, not only to the food basket of poor urban households, but also to job creation and environmental sustainability. These issues have been analyzed in the context of evolving strategies for achieving sustainable urban development, poverty alleviation and food security. Highlights: Scavenging in Kinshasa has increasing become an important livelihood source for the urban poor. This development has taken place amidst high levels of poverty, deteriorations in infrastructure and increased civil conflict. Despite the role that scavenging for solid waste plays, it is neglected in urban development and planning policy. Solid waste scavenging must be integrated in the urban development and planning policy in order to contribute to sustainable urban development.